2021
DOI: 10.1016/j.pcd.2021.06.009
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-specific diabetes worries amongst diabetic patients: The role of social support and other co-variates

Abstract: Background: The COVID-19 pandemic has impacted every individual's life. It has been shown that mortality in people with underlying diseases including diabetes has been very high. The present study aimed to measure diabetes related worries (outcome) and their associations with social support and lifestyle (exposures) amongst people with diabetes during the COVID-19 pandemic. Methods: An online cross-sectional survey was completed by 928 respondents (>18 years) between 15-11-2020 and 12-12-2020. The questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
6
23
0
Order By: Relevance
“…The broader living context for people with diabetes in the UAE, and unlike other countries, might have facilitated self-management including lack of disruption in the pharmaceutical supply chain, no difficulties in procurement of diabetes medications, no restriction in food supplies, initiatives to support patients such as the delivery of prescribed medicines to people’s homes, and the availability of telemedicine [13] , [29] . As expected and in line with similar studies in other countries, adherence to exercise was the lowest during the pandemic that mandated lockdowns and closure of sport facilities [23] , [26] , [30] .…”
Section: Discussionsupporting
confidence: 90%
“…The broader living context for people with diabetes in the UAE, and unlike other countries, might have facilitated self-management including lack of disruption in the pharmaceutical supply chain, no difficulties in procurement of diabetes medications, no restriction in food supplies, initiatives to support patients such as the delivery of prescribed medicines to people’s homes, and the availability of telemedicine [13] , [29] . As expected and in line with similar studies in other countries, adherence to exercise was the lowest during the pandemic that mandated lockdowns and closure of sport facilities [23] , [26] , [30] .…”
Section: Discussionsupporting
confidence: 90%
“…Multiple studies have reported an increase in anxiety, depression, and stress during the COVID-19 pandemic (4,13,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). One potential reason could be the pandemic's influence on the economy and workforce.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, various studies conducted with different demographics in Bangladesh reported mental health problems. For instance, anxiety, depression, panic, worry, stress, suicidal ideation, and behavioral problems (such as problematic use of smartphones, internet, and social media) were prevalent in Bangladesh (11,12,15,(31)(32)(33)(34)(35)(36)(37)(38)(39). However, the sleep quality of the general population has received comparatively little attention in studies during the pre-COVID-19 period and amidst the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%